2017
DOI: 10.1038/s41598-017-15324-6
|View full text |Cite
|
Sign up to set email alerts
|

OsMTP11 is localised at the Golgi and contributes to Mn tolerance

Abstract: Membrane transporters play a key role in obtaining sufficient quantities of manganese (Mn) but also in protecting against Mn toxicity. We have characterized OsMTP11, a member of the Cation Diffusion Facilitator/Metal Tolerance Protein (CDF/MTP) family of metal cation transporters in Oryza sativa. We demonstrate that OsMTP11 functions in alleviating Mn toxicity as its expression can rescue the Mn-sensitive phenotype of the Arabidopsis mtp11-3 knockout mutant. When expressed stably in Arabidopsis and transiently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 72 publications
0
16
0
Order By: Relevance
“…By contrast, the overexpression of OsMTP11 enhanced Mn tolerance of rice and decreased the accumulation of Mn in shoots and roots (Ma et al, 2018). Stable expression of OsMTP11-GFP in Arabidopsis and transient expression of this construct in rice and tobacco protoplasts showed that OsMTP11 was also located to the Golgi (Figure 3B; Farthing et al, 2017). However, recent studies suggested that OsMTP11 localized to the trans-Golgi network (TGN) when it was expressed in rice protoplasts and tobacco epidermal cells (Ma et al, 2018).…”
Section: Manganese Transport Proteins In Endomembranesmentioning
confidence: 96%
“…By contrast, the overexpression of OsMTP11 enhanced Mn tolerance of rice and decreased the accumulation of Mn in shoots and roots (Ma et al, 2018). Stable expression of OsMTP11-GFP in Arabidopsis and transient expression of this construct in rice and tobacco protoplasts showed that OsMTP11 was also located to the Golgi (Figure 3B; Farthing et al, 2017). However, recent studies suggested that OsMTP11 localized to the trans-Golgi network (TGN) when it was expressed in rice protoplasts and tobacco epidermal cells (Ma et al, 2018).…”
Section: Manganese Transport Proteins In Endomembranesmentioning
confidence: 96%
“…Both OsMTP8.1 and OsMTP8.2 were tonoplast-localized Mn transporters, and OsMTP9 was involved in efficient root Mn uptake (Chen et al, 2013; Ueno et al, 2015; Takemoto et al, 2017; Tsunemitsu et al, 2018b). Moreover, OsMTP11 played a crucial role in Mn tolerance through intracellular Mn compartmentalization, although the correct localization of this protein was still under debate (Farthing et al, 2017; Zhang and Liu, 2017; Ma et al, 2018; Tsunemitsu et al, 2018a). In addition, some MTP proteins from cucumber were recently isolated and their corresponding substrates were also specified.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are indications that the organelle is indeed implicated. Farthing et al (2017) showed the member of the CDF/MTP family in Oryza sativa , OsMTP11, in alleviating Mn toxicity. Moreover, the expression of OsMTP11 gene can save the Arabidopsis mtp11‐3 knockout mutant, the Mn‐sensitive phenotype.…”
Section: The Role Of Cellular Organelles In Hm Resistancementioning
confidence: 99%
“…It slightly alleviates the Zn sensitivity of the zrc1 cot1 yeast mutant and partially rescues the Mn-hypersensitivity of the pmr1 yeast mutant. Therefore, it is possible to suggest that OsMTP11 mostly functions as a Mn-CDF transporter with lower affinity for Zn (Farthing et al, 2017). It was shown that in 5-day-old seedlings of H. vulgare cv.…”
Section: Gsh and Metallothioneins Facilitate Vacuolar Sequestrationmentioning
confidence: 99%